Banana bunch cover: evaluation of promising bag materials - Sant’Anna Cordeiro da Silva, Marcela [UNESP]; Leonel, Sarita [UNESP]; Ferreira, Antonio Flávio Arruda; Souza, Jackson Mirellys Azevêdo [UNESP]; de Oliveira, Marcelo Almeida [UNESP]; Martins, Rafaelly Calsavara [UNESP]; Ferreira, Rafael Bibiano [UNESP]; de Souza Silva, Marcelo [UNESP] (Lepidus Tecnologia, 2022)
Now days there has been an increase in the consumers demand for great food, produced in environmentally cost-effective and friendly processes, being increasingly necessary new cultivation techniques able to ensure the required standards for banana growers and consumers. Therefore, the research aimed to evaluate the effects of bunch cover materials on development and quality of ‘BRS Platina’ banana fruits. The experimental design was in randomized blocks, with six treatments, four replications and four plants per plot, being the treatments: WB – without bagging; BBTK – black polypropylene bag (TNT) + kraft paper; BBPK - black polyethilene bag + kraft paper; KP – kraft paper; WBT – non-woven polypropylene white bag (TNT) and WBP - white polyethylene plastic bag. The ‘BRS Platina’ banana bunches cover improved fruits quality and the treatment polyethylene white bag (WBP) can be an advantageous option for the banana growers because of its effectiveness on the reduction of damages caused by flowers thrips (Frankliniella spp), providing a good agronomic performance and also does not delay the harvesting.
Keywords: bunches physical protection; kraft paper; Musa spp; polyethylene; polypropylene